Tripleurospermum parviflorum (Asteraceae): a new record for the flora of Greece - Goula, Katerina; Chiotelis, Charalambos; Constantinidis, Theophanis (Hacquetia, 2025)
Tripleurospermum parviflorum, recently collected on the island of Lesvos, Greece, turned out to be a new floristic record for the country. A description based on the new material is provided, together with a distribution map of all the Tripleurospermum species occurring on the island. The diagnostic features that distinguish T. parviflorum from the remaining Greek species are highlighted and the chromosome number, as well as the karyotype formula of one, out of two newly discovered populations is presented. A dichotomous key for all the Greek Tripleurospermum species facilitates proper identification. The new discovery stresses the important presence of Anatolian elements in the flora of the East Aegean Islands in general and on Lesvos, in particular.